John the Scythian – a Slayer of Usurpers and the Isaurians - Leszka, Mirosław J. (Studia Ceranea, 2020)
The paper is devoted to John the Scythian – one of the chiefs of the Byzantine army in the eighties and nineties of the 5th century. Based on the sources, the military career of John the Scythian lasted 16 years. He spent less time defending the borders of the empire and more fighting (often, victoriously) against usurpers and peoples who either had lived in its territory for centuries (the Isaurians) or sought a place to settle there (the Ostrogoths), and whose status kept changing from ally to enemy. John, as evidenced by his nickname, came from a barbarian people, but this did not prevent him from serving the emperor loyally and building his position in the circles of the empire’s elite.